An investigation into the effects of macromolecular crowding on the kinetics of upper glycolytic enzymes in Saccharomyces cerevisiae - Wissing, Julian (Stellenbosch : Stellenbosch University, 2020)
Thesis (MSc)--Stellenbosch University, 2020.